High-throughput screening of transition metal single-atom catalyst anchored on Janus MoSSe basal plane for hydrogen evolution reaction. (8th March 2021) - Xiao, Chengwei; Sa, Rongjian; Ma, Zuju; Cui, Zhitao; Du, Wei; Sun, Xueqin; Li, Qiaohong; Deng, Hailiang
Abstract: Considerable efforts have been made to enhance the hydrogen evolution reaction (HER) catalytic performance of Janus MoSSe monolayer, which have been considered to be a promising candidate due to the unique asymmetry structure. However, the activation effect remains non-optimal for the inert Janus MoSSe basal plane at present. Herein, a train of transition metal (TM) atoms were anchored on the S-/Se-/Mo-defective MoSSe basal plane to screen effective TM single-atom catalysts for HER through density functional theory (DFT) computations. Interestingly, the single Co atom anchored on Mo-defective MoSSe and the single Zn or Cd atom anchored on S-defective MoSSe were judged to possess excellent HER performance yielding a near-zero ΔGH (ΔGH = −0.050, −0.095, −0.098 eV, respectively), which is comparable to the optimized Pt-SACs. The enhanced HER activity is attributed to the doping of TM atoms (Co, Zn and Cd) which improves the conductivity of the original MoSSe and offers unoccupied states near the Fermi level decreasing the energy barrier of electrons transfer between H and TMs@MoSSe surface. In addition, the change of unoccupied antibonding states of active atoms leads to appropriate interaction between the active sites and H. The hybridization between H- s orbital and the TMs@MoSSe systems around the Fermi level also suggests the formation of stable bonding-antibonding hydrogen adsorption states. This work reveals an effective way of activating MoSSe basal plane for HER. Graphical abstract: Based on DFT, the Co/Zn/Cd atoms (from Ti to Zn and from Zr to Cd) were screened out to activate the MoSSe inert basal plane for HER. Image 1 Highlights: Screening of transition metal single-atom catalyst on MoSSe surface for HER. Co, Zn, and Cd doping yield near-zero ΔGH . The H and TMs@MoSSe systems form stable bonding-antibonding adsorption states. The unoccupied states of TM atoms decrease the energy barrier of electron transition.